Drought resilience of conifer species is driven by leaf lifespan but not by hydraulic traits. Issue 3 (12th May 2022) - Song, Yanjun; Sterck, Frank; Zhou, Xiaqu; Liu, Qi; Kruijt, Bart; Poorter, Lourens
Summary: Increased droughts impair tree growth worldwide. This study analyzes hydraulic and carbon traits of conifer species, and how they shape species strategies in terms of their growth rate and drought resilience. We measured 43 functional stem and leaf traits for 28 conifer species growing in a 50‐yr‐old common garden experiment in the Netherlands. We assessed: how drought‐ and carbon‐related traits are associated across species, how these traits affect stem growth and drought resilience, and how traits and drought resilience are related to species' climatic origin. We found two trait spectra: a hydraulics spectrum reflecting a trade‐off between hydraulic and biomechanical safety vs hydraulic efficiency, and a leaf economics spectrum reflecting a trade‐off between tough, long‐lived tissues vs high carbon assimilation rate. Pit aperture size occupied a central position in the trait‐based network analysis and also increased stem growth. Drought recovery decreased with leaf lifespan. Conifer species with long‐lived leaves suffer from drought legacy effects, as drought‐damaged leaves cannot easily be replaced, limiting growth recovery after drought. Leaf lifespan, rather than hydraulic traits, can explain growth responses to a drier future.